Islamic Scientific Tradition in the Modern Era: A Phenomenological Study on the Integration of Education in Islamic Boarding Schools and Higher Education - Zahroh, Aminatuz; Pramuja, Alvin Dian (Sekolah Tinggi Agam Islam Sumatera Medan, 2025)
This research explores the scientific tradition built at Pondok Pesantren Putri Syarifuddin, Wonorejo Lumajang, focusing on the core values instilled and efforts to strengthen the scientific tradition in the pesantren. Based on a qualitative approach with observation, interview, and documentation study techniques, the results showed that this pesantren succeeded in instilling values such as curiosity, analytical skills, openness to other people's opinions, and independence in thinking. The pesantren's efforts in the recitation of the yellowIslamic classic book, the translation movement, scientific works, and other scientific programs contribute to increasing scientific awareness, teaching quality, and understanding of santri. The implication of these efforts is the development of a scientific tradition in pesantren, increasing santri confidence in discussion, and strengthening the role of alumni in the world of education. This research shows that the scientific tradition in pesantren can go hand in hand and strengthen each other with the scientific tradition in higher education. The implication of this research is that the scientific tradition in pesantren is growing with the increasing participation of santri in scientific activities. This research contributes to improving the quality of teaching in and strengthening the role of alumni in the world of community education.